Konsep Harta dan Kepemilikan dalam Perspektif Islam - masrina masrina (ITB AAS INDONESIA Surakarta, 2023)
Islam is a perfect religion covering all areas of human life. Assets in the Islamic economic system have an important position. In maqashid sharia, namely maintaining or guarding property, this is God's purpose and purpose in order to provide benefits to humans to be used as guidelines in doing business and muamalah. The use of wealth in Islamic teachings must always be in the service of Allah and used in the context of taqarrub (get closer) to Allah. The method of activity carried out is a literature review approach by examining the normative laws of the Shari'a originally based on the Qur'an and then strengthened by the ijtihad of the opinions of fiqh scholars regarding the concept of property and ownership in an Islamic perspective. According to the majority of scholars, property is something that has value, it is obligatory to replace it for those who damage it, and it is permitted by the Shari'ah to use it when it is not an emergency. Thus, something that has no value among humans and which is not permitted by the Shari'ah is not considered a property. Ownership is syara' law that applies to certain objects or uses, which allows anyone who gets them to take advantage of the goods, as well as obtain compensation from the goods.